Pengaruh Work Life Balance Dan Disiplin Kerja Terhadap Kinerja Karyawan Pt.Perkebunan Nusantara Iv Regional Iii Kebun Sei Tapung - Fransiskus Nababan; Khairunnisak Khairunnisak; Wan Rizca (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of work-life balance and work discipline on employee performance at PT Perkebunan Nusantara IV Regional III Kebun Sei Tapung. The research was motivated by fluctuating employee performance, particularly delays in completing tasks and imbalances between personal life and work responsibilities. A quantitative research approach was employed, with a sample of 86 respondents selected using purposive sampling. Data were collected through questionnaires and interviews and analyzed using multiple linear regression. The results indicate that work-life balance has a positive and significant effect on employee performance. Work discipline also shows a positive and significant effect on employee performance. Simultaneously, work-life balance and work discipline significantly influence employee performance. These findings highlight that maintaining a balance between personal and work life, along with consistent discipline, are crucial factors for improving employee productivity and overall performance. The company is encouraged to enhance policies that support work-life balance and consistently strengthen work discipline to achieve optimal performance outcomes.